KONSERVATISME AKUNTANSI, STRUKTUR MODAL, INTENSITAS ASET TETATP, DAN TRANSFER PRICING, PENGARUHNYA TERHADAP TAX AVOIDANCE: ACCOUNTING CONSERVATISM, CAPITAL STRUCTURE, FIXED ASSET INTENSITY, AND TRANSFER PRICES, ITS EFFECT ON TAX AVOIDANCE - Felisya, Suci Rahmatul; Afrizal, Afrizal; Erawati, Misni (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2023)
The study's focus is on identifying the many elements that lead to tax evasion, including but not limited to accounting conservatism, capital structure, the value of fixed assets, and transfer pricing. Tax avoidance refers to the strategies used by businesses and people to minimize their tax obligations. This study focuses on Indonesian mining firms that had an IPO between 2015 and 2022 on the Indonesia Stock Exchange. Thirteen companies were selected as study samples after meeting selection criteria and using a purposive random sampling method. This study used multiple linear regression as its analytic tool. The results suggest that capital structure and transfer pricing play key roles in evading taxation. While the number of fixed assets and the degree of accounting conservatism have only a little role in facilitating tax avoidance